2014
DOI: 10.1021/ef500218x
|View full text |Cite
|
Sign up to set email alerts
|

How Naturally Adsorbed Material on Minerals Affects Low Salinity Enhanced Oil Recovery

Abstract: Laboratory core flood and field scale tests have demonstrated that about 5 to 40% more oil can be released from sandstone reservoirs by injecting low salinity water, rather than high salinity fluids such as seawater or formation water. The effect has been explained by a change in wettability of the minerals that form the pore wall, as a result of the decrease in divalent cation concentration. Using X-ray photoelectron spectroscopy, we have demonstrated that even for solvent cleaned core samples, mineral surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(92 citation statements)
references
References 32 publications
8
84
0
Order By: Relevance
“…Although the particles came from the same reservoir core plug, their topography and surface composition were very different. The images were consistent with images taken by other researchers on material from the same core plug and from different samples 13,16 . Fig.…”
Section: Dlvo Theorysupporting
confidence: 89%
See 1 more Smart Citation
“…Although the particles came from the same reservoir core plug, their topography and surface composition were very different. The images were consistent with images taken by other researchers on material from the same core plug and from different samples 13,16 . Fig.…”
Section: Dlvo Theorysupporting
confidence: 89%
“…Recent work, for example, has demonstrated that adsorbed organic compounds, which are associated with all natural surfaces, change wetting properties 13,14 . Although crude oil is a complex mixture of many organic compounds, it is primarily the functional groups that deter- mine which adhere on the pore surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion is an indication of the attractive interactions between the brine/oil and brine/quartz interfaces of thin brine films in reservoir rocks. Diluting the brine makes the quartz surface more water-wet and reduces the adhesion to oil [35]. The experimentally measured adhesion force as a function of salinity can be fitted well with force predictions from DLVO theory [36 • ].…”
Section: Zeta Potential Contact Angle Oil Recovery and Afm Measurementioning
confidence: 86%
“…For the low salinity solution, we simply diluted the stock high salinity solution by about 25 times, to produce a solution that was 1,500 ppm. We also used synthetic formation water that we made to reflect the composition of the water that was present in the oil reservoir where the core was taken, before the oil was produced, composition is published in Matthiesen et al (Matthiesen et al 2014). The solutions were made by dissolving the salts in ultrapure deionised water (MilliQ) that had resistivity >18 M ·cm.…”
Section: Methodsmentioning
confidence: 99%